2006
DOI: 10.7202/012140ar
|View full text |Cite
|
Sign up to set email alerts
|

Quand le malheur frappe les bénéficiaires de la sécurité du revenu. Sur qui peuvent-ils s’appuyer ?

Abstract: Cette étude analyse les conditions de réalisation du soutien social dans les quartiers de Saint-Henri et de la Pointe Saint-Charles, en comparant un groupe de 61 prestataires de la sécurité du revenu avec un échantillon de 21 personnes de la population vivant au-dessus du seuil de la pauvreté, et en fonction du degré de détresse dans chaque groupe. Elle vise également à décrire comment une adversité vécue par les prestataires avec ou sans détresse vient briser ou modifier le réseau de soutien. Les résultats in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
1
0
2
Order By: Relevance
“…The survey confirmed what most epidemiological studies conducted around the world have concluded to date: people belonging to the lowest socio-economic level of our society are the most vulnerable to psychological distress [42-44]. There is considerable evidence that underprivileged groups are affected by chronic stress and more negative life events [11,44]; their social networks are not as strong and reliable as higher income groups [9,45]. …”
Section: Discussionsupporting
confidence: 75%
“…The survey confirmed what most epidemiological studies conducted around the world have concluded to date: people belonging to the lowest socio-economic level of our society are the most vulnerable to psychological distress [42-44]. There is considerable evidence that underprivileged groups are affected by chronic stress and more negative life events [11,44]; their social networks are not as strong and reliable as higher income groups [9,45]. …”
Section: Discussionsupporting
confidence: 75%
“…The perceived availability of emotional support from their social network and a smaller number of harmful persons are the two variables most strongly associated with better mental health. A high concentration of poor residents subjected to conditions of chronic stress related to the precariousness of their living conditions is clearly not conducive to obtaining adequate social support when stress-inducing life events occur, as was demonstrated by Tousignant and Caron 62 in these same neighbourhoods. Very high levels of psychological distress were found among these neighbourhoods' poor residents but also among their other residents, who have a much higher level of distress than the general population on the Island of Montreal.…”
Section: Discussionmentioning
confidence: 94%
“…Des études démontrent également que ces populations subissent plus fréquemment des événements de vie générateurs de stress (mort d'un proche, accidents, maladie, divorce, perte d'emploi) que les populations mieux nanties. De plus, de nombreuses recherches signalent, chez les populations à faible revenu, une carence dans le soutien social disponible (pour une recension de l'ensemble de ces relations, voir Tousignant et Caron, 2005).…”
Section: Les Populations Pauvresunclassified
“…Deux prédicteurs de la qualité de vie des personnes souffrant de schizophrénie et liés au soutien social ont été identifiés, il s'agit du soutien émotif et du soutien de valorisation personnelle. L'importance de ces deux dimensions du soutien pour la qualité de vie de ces personnes, a été confirmée par Caron et al (2005) dans une étude auprès de 143 personnes souffrant de schizophrénie. Ces deux prédicteurs se sont montrés les meilleurs parmi 16 variables incluses dans un modèle de prédiction (démogra-phiques, cliniques, stresseurs, coping, sévérité des symtômes, soutien social).…”
Section: La Schizophrénieunclassified